PEDIATRIC ORTHOPAEDIC TRAUMA AND ASSOCIATED INJURIES AT AN INNER-CITY LEVEL 1 TRAUMA CENTER. Issue 7 (30th July 2021) - Levidy, Michael; Rai, Rahul; Chu, Alice; Kaushal, Neil; Edobor-Osula, O. Folorunsho
Background/Purpose: Pediatric orthopaedic trauma in inner city communities often present with unique and modifiable risk factors. The purpose of this study was to characterize and evaluate the pattern and nature of orthopaedic and associated injuries in pediatric patients involved in motor vehicle accidents (MVA), falls, sports related injuries and pedestrian struck either on foot or on bicycle at an inner-city level 1 trauma center. Methods: 260 pediatric patients who presented to the emergency department after a fall, a sports related injury, MVA, pedestrian struck on foot (PSoF), or pedestrians struck on bicycle (PSoB) with orthopaedic injuries at our institution between 2013 and 2020 were retrospectively reviewed. Results: The mean age of our cohort was 9.1 years (SD ±4.60). 36.5% (95/260) were girls, 63.5% (165/260) were boys. There were a total of 260 patients with a total of 331 fractures. 96.3% (319/331) of the fractures were appendicular while 3.6% (12/331) were axial. 43.8% (114/260) of patients had lower extremity fractures and 49.2% (128/260) had upper extremity fractures. Of all mechanisms, MVAs were most commonly associated with axial fractures (p<0.01). Falls were associated most commonly with upper extremity fractures (p<0.01), lower patient age (p<0.01) and negatively correlated with lower extremity fractures (p<0.01). Sports related injuries were most commonly correlated with tibia fractures (p<0.01). Sports etiologies were subdivided into Basketball (29%), Football (27%), Soccer (11%), and other physical activities like Rollerblading (11%) and Skateboarding (9%). PSoF was associated with tibia fractures (p<0.05) and open fractures (p<0.01). PSoB was the most likely mechanism to lead to lower extremity fractures (p=0.01) and head trauma (p<0.01). 75% (6/8) of PSoB were not wearing a helmet at the time of injury. Conclusion: Not surprisingly, falls represent the most common mechanism of pediatric orthopaedic injury. Other mechanism of injuries included MVAs, pedestrian struck on foot or bicycle were associated with more significant trauma including vertebral fractures, open fractures, head trauma and compartment syndrome. Preventative measures including education on car seat and seat belt use, helmet use and bicycle safety in children may reduce the incidence of these serious injuries. : Figure 1. – Mechanism of Injury on a patient basis. Asterisk signifies statistical significance.